Intervallo Nello spazio e nel tempo d’un sogno (Altre Modernità, 2017)
Two fugitives find themselves in a garden, a place clearly created by man, waiting for someone to pick them up and give them a new possibility, a new life. Two different people, with different expectations from life and very different dreams for the future, wait for something to happen, ready to seize the moment. That is what the whole play is about: sometimes people need to escape, to leave everything behind, it is all they crave for, but, sometimes, even if they have the chance to do so, they lack the courage to do it for real. When all you know is murder, theft and crime, it is difficult to dream of something better, and sometimes, the dream abruptly ends, revealing what is real and what is not.